2022
DOI: 10.1590/1413-81232022277.19932021en
|View full text |Cite
|
Sign up to set email alerts
|

Association between zinc deficiency and cognitive decline in community-dwelling older adults

Abstract: This is a cross-sectional study evaluating the association between zinc deficiency and cognitive decline in 591 community-dwelling older adults living in the cities of Campinas, Limeira, and Piracicaba-SP. Cognitive status was evaluated using the Cognitive Abilities Screening Instrument-CASI-S, considering a decline for scores <23 for those aged 60-69 and <20 for those aged ≥70 years. Among the evaluated cognitive domains, older adults with zinc deficiency had significantly lower mean scores on the memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…We found that zinc supplementation was associated with a lower risk of all-cause dementia and Alzheimer’s disease, independent of demographic information, lifestyle factors, APOE4, cardiometabolic disorders, and depression. A cross-sectional analysis of 591 community-dwelling older adults found that zinc deficiency was associated with a higher prevalence of cognitive decline ( 19 ). In another cross-sectional study of 2,450 participants aged 60 years or older from the National Health and Nutrition Examination Survey 2011–2014, zinc intake was non-linearly associated with cognitive function ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that zinc supplementation was associated with a lower risk of all-cause dementia and Alzheimer’s disease, independent of demographic information, lifestyle factors, APOE4, cardiometabolic disorders, and depression. A cross-sectional analysis of 591 community-dwelling older adults found that zinc deficiency was associated with a higher prevalence of cognitive decline ( 19 ). In another cross-sectional study of 2,450 participants aged 60 years or older from the National Health and Nutrition Examination Survey 2011–2014, zinc intake was non-linearly associated with cognitive function ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the results of our study do not support the establishment of causal relationships because of the observational design. Thirdly, while several cross-sectional studies have explored the potential dose–response relationship of antioxidant supplementation in relation to cognitive impairment ( 8 , 16 , 19 ), there is relatively limited information available about the link between the duration of antioxidant supplementation and cognitive impairment or dementia ( 9 , 16 ). We could not examine these associations in our study given the lack of relevant data.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previously this was associated with the decreased probability of micronutrient adequacy, including calcium, folate, iron, vitamin A, vitamin C, and zinc [ 18 ]. Many of these nutrients are essential for the brain [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, vegan diets, which exclude all animal products, were associated with a low intake of vitamins B 2 , niacin (B 3 ), B 12 , D, iodine, zinc, calcium, potassium, selenium, and protein [ 19 ]. This is concerning, as an inadequate intake of these nutrients was associated with poorer mood [ 20 , 21 , 22 ], cognitive functioning [ 21 , 23 , 24 ], and a predisposition towards cognitive decline [ 25 , 26 , 27 ]. The adequate intake of these nutrients is particularly crucial during pregnancy to regulate neurodevelopment [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the cerebral cortex is involved in high levels of cognitive functions, alterations in Zn 2+ levels within this area could impact cognitive performance in elderly individuals (Vogler et al, 2022). Fluctuations in Zn 2+ distribution, transport, and signaling may contribute to age-related cognitive decline, neurodegenerative diseases, and other age-related neuropathological conditions and psychiatric disorders (Takeda et al, 2018;Marchetti et al, 2022). The level of Zn 2+ in the brain is essential to support neuronal growth, synaptic plasticity, and cognitive development.…”
Section: Zn 2+ As a Function Of Agementioning
confidence: 99%